Controlling Bowing and Narrowing in SiO2 Contact-Hole Etch Profiles Using Heptafluoropropyl Methyl Ether as an Etchant with Low Global Warming Potential - You, Sanghyun; Yang, Hyun Seok; Jeon, Dongjun; Chae, Heeyeop; Kim, Chang Koo (Coatings, 2023)
Heptafluoropropyl methyl ether (HFE-347mcc3), as a lower-GWP (global warming potential) alternative to PFCs (perfluorocarbons), was used to etch SiO2 contact holes. The etch profiles of the SiO2 contact holes in HFE-347mcc3/O2/Ar plasmas showed more bowing at lower flow rate ratios of HFE-347mcc3 to Ar, whereas more narrowing occurred at higher ratios. The measurements of the angular dependences of the deposition rates of fluorocarbon films on the surface of SiO2 and the etch rates of SiO2 showed that the shape evolution of contact-hole etch profiles at different HFE-347mcc3/Ar ratios was attributed to an increase in etch resistance and a decrease in etch ability of the sidewalls of the contact hole with the increasing HFE-347mcc3/Ar ratio. This resulted in determining the optimum ratio of HFE-347mcc3 to Ar to achieve the maximum anisotropy of the contact hole etched in HFE-347mcc3/O2/Ar plasmas. By carefully selecting the specific flow rates of HFE-347mcc3/O2/Ar (9/2/19 sccm), a highly anisotropic and bowing-free SiO2 contact hole, with a 100 nm diameter and an aspect ratio of 24, was successfully achieved.
Keywords: contact-hole etching; global warming potential; heptafluoropropyl methyl ether; perfluorocarbon; plasma etching